Pengaruh Terapi Musik terhadap Penurunan Tingkat Stress Kerja Perawat di Unit Perawatan Kritis - Maryana; Sri Ariani; Eko Suryani (Jurnal Keperawatan Notokusumo, 2014)
Background: Stress is state of being produced by changing environment and accepted as a thing challenge threatening or destructive balance. Stress can cause negatif feelings or contrary to what is desired or threatened the emosional well-being of a person. Critical care nurse are susceptible to stress because it faced the routine care of patients in critical condition and require strict monitoring. Music therapy is beneficial to improve relaxation and give flavor comfortable so as to hinder sensation angsty, fear, tension and divert attention from thoughts unpleasant. Objective: This research aims to know the influence of music therapy to decrease stress levels nurses work in critical care units. Method: Quasi-experimental study design with pretest and posttest without control design. Population: all of associate nurse. Time research 12 weeks. Measurement of the level of work stress using the questionnaire work stress. Hypothesis test with wilcoxon test with significance level p?0,05. Result: Having given music therapy the majority have low levels of work stress 88,8%. Music therapy has an effect on the decrease in work stress p 0.000 or p<0,05. Music therapy has an effect on the decrease in mean pulse, mean systolic blood pressure and mean MAP. Conclusion: Music therapy is capable of lowering the levels of work stress of nurses in Critical Care Unit